Energisystem med utnyttjande av restprodukter för gödsling av Salixodling för energiproduktion : studier av kretslopprojektet i Enköping och dess applicering på en kommun i Ryssland. - Korneevets, Olga (SLU/Dept. of Energy and Technology, 2008)
The purpose of this work is to study a circulation project in Enköping municipality, where the society’s rest products are used to make beneficial products. In Enköping the rest products from waste treatment plants and private sewers are used to fertilize and irrigate Salix plantations that later are harvested and burned at the local combined heating and power plant, ENA Energy AB, to produce electricity and heat. Possibilities to apply this kind of project on a municipality in Russia are also explored.